Confirmation of Transgenic Robusta Coffee (Coffea canephora) Transformed by Chitinase-encoding Gene and Its Propagation Through Somatic Embryogenesis - Priyono .; Asmini Budiani; Surip Mawardi (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2005)
Genetic engineering of Robusta coffee resistant to fungal diseases might be done by introducing a chitinase-encoding gene into genome of this plant. This research was aimed to confirm transgenic plant of BP 308 clone Robusta coffee transformed by chi gene and to evaluate its ability for the somatic embryogenesis. Confirmation of transgenic was carried out by analysis the presence of NPTII gene as a selectable marker for Canamysin resistant using PCR technique. The somatic embryo initiation and reproduction were evaluated in 11 plant accessions. Three kinds of sucrose concentration, 20%, 30% and 40% were applied in initiation stage of somatic embryo germination. The suitability of 4 medium, namely M1 (without addition by liquid medium), M2 (addition by liquid medium contained 0.25 mg/l kinetin), M3 (addition by liquid medium contained 0.25 mg/l IAA) and M4 (addition by liquid medium contained 0.25 mg/l GA3 ) was evaluated for somatic embryo maturation. The result showed that 8 out of 10 plant accessions tested were transgenic and they could be propagated through somatic embryogenesis. The ability of transgenic plant for somatic embryo initiation, reproduction and regeneration were similar with that of nontransgenic one. Germination of somatic embryo could be improved by using 40% sucrose. Maturation of somatic embryo could be improved by addition of fresh liquid medium on the ancient gelled medium that used for somatic embryos reproduction. The best result was obtained on addition of fresh medium contained 0.25 mg/l GA 3 in which 65% of the somatic embryos developed to pre-germinate somatic embryo. Key words: Coffea canephora, transgenic plant, somatic embryogenesis.